Patient Perceptions and Trust in Artificial Intelligence for Radiology Services: Evidence from Indriati Solo Baru Hospital - Devanti Octavia Ellyamurti; Radityo Fajar Arianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Artificial Intelligence (AI) has emerged as a transformative innovation in radiology, offering faster and more accurate diagnostic capabilities. However, patient acceptance and trust remain critical challenges that influence its successful implementation. This study aims to analyze the factors influencing patients’ perceptions and trust in the use of AI in radiology services at Indriati Hospital Solo Baru. This study uses a quantitative survey design with a cross-sectional approach and involves 153 respondents who underwent AI-based MRI examinations. Data was collected using a Likert-scale questionnaire with purposive sampling and analyzed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method. The analysis results show that trust, efficiency, and being informed have a positive influence on perceived usefulness and perceived ease of use. Additionally, perceived usefulness and perceived ease of use increase the intention to use AI in radiology. The variables of transparency, data security, and privacy were also proven to strengthen the influence of trust on the intention to use AI in radiology. This finding confirms that benefits, convenience, trust, and assurances of transparency and data security significantly influence patient acceptance of AI.